Evaluating the effectiveness of a novel somatostatin receptor 2 antagonist, ZT-01, for hypoglycemia prevention in a rodent model of type 2 diabetes - D’Souza, Ninoschka C.; Aiken, Julian A.; Hoffman, Emily G.; Atherley, Sara C.; Champsi, Sabrina; Aleali, Nadia; Shakeri, Dorsa; El-Zahed, Maya; Akbarian, Nicky; Nejad-Mansouri, Mehran; Bavani, Parinaz Z.; Liggins, Richard L.; et al. (Frontiers in Pharmacology, 2024)
Background: Elevated levels of somatostatin blunt glucagon counterregulation during hypoglycemia in type 1 diabetes (T1D) and this can be improved using somatostatin receptor 2 (SSTR2) antagonists. Hypoglycemia also occurs in late-stage type 2 diabetes (T2D), particularly when insulin therapy is initiated, but the utility of SSTR2 antagonists in ameliorating hypoglycemia in this disease state is unknown. We examined the efficacy of a single-dose of SSTR2 antagonists in a rodent model of T2D. Methods: High fat fed (HFF), low dose streptozotocin (STZ, 35 mg/kg)-induced T2D and HFF only, nondiabetic (controls-no STZ) rats were treated with the SSTR2 antagonists ZT-01 /PRL-2903 or vehicle (n=9-11/group) 60 minutes before an insulin tolerance test (ITT; 2-12U/kg insulin aspart) or an oral glucose tolerance test (OGTT; 2g/kg glucose via oral gavage) on separate days. Results: This rodent model of T2D is characterized by higher baseline glucose and HbA1c levels relative to HFF controls. T2D rats also had lower c-peptide levels at baseline and a blunted glucagon counterregulatory response to hypoglycemia when subjected to the ITT. SSTR2 antagonists restored the glucagon response and reduced incidence of hypoglycemia, which was more pronounced with ZT-01 than PRL-2903. ZT-01 treatment in the T2D rats increased glucagon levels above the control response within ~60 minutes of dosing, and values remained elevated during the ITT (glucagon Cmax: 156 ± 50 vs 77 ± 46 pg/mL, p<0.01). Hypoglycemia incidence was attenuated with ZT-01 vs. controls (63 vs 100%) and average time to hypoglycemia onset was also delayed (103.1± 24.6 vs 66.1 ± 23.6 min, p<0.05). ZT-01 administration at the OGTT onset increased the glucagon response but without exacerbating hyperglycemia (2877 ± 806 vs 2982 ± 781), potentially due to the corresponding increase in c-peptide levels (6251 ± 5463 vs 14008 ± 5495, p=0.013). Conclusion: Treatment with SSTR2 antagonists increases glucagon responses in a rat model of T2D and results in less hypoglycemia exposure. Future studies are required to determine the best dosing periods for chronic SSTR2 antagonism treatment in T2D.